A Generic Approach towards PyTorch and Its Data Structure Tensor through Deep Learning - Gadicha, Dr. Ajay B (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 3 No 1 (2019): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
PyTorch is a library for python programs that simplifies building deep learning projects. It emphasizes flexibility and allows deep learning model to express in idiomatic python. This adoptability and ease of use found early adopters in the research society, and in the years since the library released it has grown into one of the most prominent deep learning tools for broad range of application. This paper expresses the knowledge about the core data structure use by pytorch i.e. Tensor. It is a multidimensional array that has many resemblances with Numpy array. Tensor accelerates mathematical operations and Pytorch has packages for distributed training and extensive library of deep learning function. How to cite this article: Gadicha AB, Gadicha VB. A Generic Approach towards PyTorch and Its Data Structure Tensor through Deep Learning. J Adv Res Appl Arti Intel Neural Netw 2019; 3(1): 25-29.